Analysis of Visual Field Defects Obtained with Semiautomated Kinetic Perimetry in Patients with Leber Hereditary Optic Neuropathy. (21st March 2018) - Nowomiejska, Katarzyna; Kiszka, Agnieszka; Koman-Wierdak, Edyta; Tonska, Katarzyna; Maciejewski, Ryszard; Jünemann, Anselm G.; Rejdak, Robert
Abstract : Purpose. To analyse visual field (VF) defects obtained using semiautomated kinetic perimetry (SKP) in patients suffering from Leber hereditary optic neuropathy (LHON). Methods. Twenty-two eyes of eleven consecutive LHON male patients with confirmed mitochondrial 11778G>A DNA mutation were prospectively examined with the V4e stimulus of SKP in both eyes. The mean time after the onset of LHON was one year. The area of obtained isopters was measured in square degrees (deg 2 ). Additionally, static automated perimetry (SAP) within 30° was performed. Results. Visual acuity ranged from counting fingers to 50 cm to 0.4. VFs obtained with SKP showed central scotomas in 18 eyes (82%); the periphery of the VF in these eyes remained intact. The mean area of central scotoma was 408.8 deg 2, and the mean area of the peripheral VF was 12291.1 deg 2 ; SAP also revealed central scotoma in these patients. In four eyes (18%) with the worst visual acuity, only the residual central island of VF was found using SKP (mean area 898.4 deg 2 ). SAP was difficult to obtain in these patients. Conclusions. SKP provides additional clinical information in regard to the visual function of LHON patients. SKP enables the quantification of the area of central scotoma, preserved peripheral VF, and residual central island of vision. Using V4 stimulus is especially useful in LHON patients with poor visual acuity, when SAP is difficult to obtain.